Primary Pericardial Sarcoma with Right Atrial Invasion and Multiple Bilateral Pulmonary Metastases in a Patient with Hereditary Nonpolyposis Colorectal Cancer. (21st November 2016) - Wong, Eugene; Oh, Lawrence J.; Nahar, Kazi; Lee, Adrian; Clarke, Stephen
Abstract : Primary tumours originating from the pericardium are extremely rare. Previous studies have reported that these tumours account for only 6.7–12.8% of all mediastinal tumours with an overall prevalence of 0.001% to 0.007%. The majority of these tumours are benign lipomas or pericardial cysts. The most common pericardial malignancy is mesothelioma. Sarcomas are soft-tissue mesenchymal malignancies originating from various parts of the body but are extremely rare in this area. We report a case of a 52-year-old female who was diagnosed with a primary sarcoma with rhabdoid differentiation originating from the pericardium. The patient presented to her GP with a four-week history of progressive dyspnea and chest pain on exertion. Chest X-Ray demonstrated a prominent pericardial effusion and suspicious chest and pericardial lesions. Biopsies of the effusion and primary tumour identified on FDG/PET scans revealed the diagnosis of primary undifferentiated sarcoma. On thoracotomy, it was noted that the tumour had invaded the right atrium; therefore, pericardial window was aborted and a drain inserted instead. The patient was then started on chemotherapy; however, progression soon occurred and the patient died within 4 months, suggesting there is urgent need for efficacious treatments for sarcomatous lesions.